New perspectives in the Italian property market: the funeral sector. Issue 4 (15th May 2019) - Morena, Marzia; Truppi, Tommaso; Ierecitano, Verdiana; Lorusso, Gianluca
Abstract : Purpose: The purpose of this paper is to investigate a particular type of property market, that of funeral homes, of which little is known, despite the fact that it is an expanding market, reflecting a social and cultural change in Italy. Design/methodology/approach: A qualitative analysis of the funeral property market was carried out. Information and data were collected from funeral companies, with reference to their market strategy, and from institutional investors, in order to gauge their knowledge of that specific sector and their willingness to invest in this specific property type. The instruments used were questionnaires, telephone interviews and on-site visits. Findings: The results of this study suggest that Italian funeral companies identified a new property market, responding to the demands of a changing social context, especially in Northern Italy. Limited experience in the management of this asset and the lack of a clear and uniform legislative regulation at the national level appear to be among the main difficulties. From the investors' point of view, the main problems in investing in this property were the lack of adequate knowledge in the sector and moral qualms about the specific type of assets. Research limitations/implications: The small sample restricts generalization beyond the companies that participated in the research. Furthermore, the research only focused on the private sector related to niche market strategy and property investments. Practical implications: The paper could raise awareness of a specific and not well-known property market among the real estate operators. Originality/value: The originality of the analysis lies in investigating a relevant phenomenon from the social point of view that has been little or not at all addressed from the point of view of real estate, particularly in Italy.